2021
DOI: 10.31236/osf.io/e7tvr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compatibility of concurrent aerobic and strength training for skeletal muscle size and function: an updated systematic review and meta-analysis

Abstract: ObjectiveThis systematic review assessed the compatibility of concurrent aerobic and strength training compared to sole strength training regarding adaptations in muscle function (maximal and explosive strength) and muscle mass. Subgroup analyses were conducted to examine the impact of training modality, exercise type, exercise order, training frequency, age, and training status.DesignA systematic literature search was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…More recently, alongside further considerations of the exact nature of the concurrent training programs design, others have discussed possible participant level characteristics (e.g., training status, sex, nutritional practices) or other methodological factors (e.g., measurement approaches used for outcomes) that might also explain some of the heterogeneity across studies Despite the historical variation in findings of individual concurrent training studies, and the contrasting conclusions of earlier reviews and meta-analyses, a recent updated systematic review and meta-analysis offers insight into the existence, or lack thereof, for an 'interference' effect. Schumann et al (223) identified 15 studies that employed concurrent aerobic and RT (including 201 participants) and RT alone (including 188 participants). Their overall random effects model found a standardized between condition treatment effect of -0.01 [95% CI -0.16 to 0.18] suggesting no more than a trivial difference at best.…”
Section: Concurrent Trainingmentioning
confidence: 99%
“…More recently, alongside further considerations of the exact nature of the concurrent training programs design, others have discussed possible participant level characteristics (e.g., training status, sex, nutritional practices) or other methodological factors (e.g., measurement approaches used for outcomes) that might also explain some of the heterogeneity across studies Despite the historical variation in findings of individual concurrent training studies, and the contrasting conclusions of earlier reviews and meta-analyses, a recent updated systematic review and meta-analysis offers insight into the existence, or lack thereof, for an 'interference' effect. Schumann et al (223) identified 15 studies that employed concurrent aerobic and RT (including 201 participants) and RT alone (including 188 participants). Their overall random effects model found a standardized between condition treatment effect of -0.01 [95% CI -0.16 to 0.18] suggesting no more than a trivial difference at best.…”
Section: Concurrent Trainingmentioning
confidence: 99%